2001
DOI: 10.1002/kin.10020
|View full text |Cite
|
Sign up to set email alerts
|

Chemical kinetic modeling study of shock tube ignition of heptane isomers

Abstract: High-temperature detailed chemical kinetic reaction mechanisms are developed for all nine chemical isomers of heptane (C 7 H 16 ), following techniques and models developed previously for other smaller alkane hydrocarbon species. These reaction mechanisms are tested by computing shock tube ignition delay times for stoichiometric heptane/oxygen mixtures diluted by argon. Although no corresponding experiments have been reported in the literature for most of these isomers of heptane, intercomparisons between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
56
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 27 publications
(46 reference statements)
3
56
0
Order By: Relevance
“…This agrees with past shock tube ignition delay experiments of Smith et al [31] and computed results of Westbrook et al [8,9] that showed that the ignition delay times for all of the heptane isomers, whose octane numbers range from 0 to 112, have nearly identical ignition delay times at high temperatures. The differences in ON for these isomers do not produce different ignition delay times at high temperatures.…”
Section: Primary Reference Fuel Mechanism Calculationssupporting
confidence: 91%
See 2 more Smart Citations
“…This agrees with past shock tube ignition delay experiments of Smith et al [31] and computed results of Westbrook et al [8,9] that showed that the ignition delay times for all of the heptane isomers, whose octane numbers range from 0 to 112, have nearly identical ignition delay times at high temperatures. The differences in ON for these isomers do not produce different ignition delay times at high temperatures.…”
Section: Primary Reference Fuel Mechanism Calculationssupporting
confidence: 91%
“…Selection of these two pairs of specific fuels, which are termed "Primary Reference Fuels" or PRFs, reflects the fact that diesel fuels are typically much heavier than gasolines, with hydrocarbon molecules correspondingly larger in diesel fuels. Thus the PRF components assigned to diesel fuel are both C 16 molecules, relecting the average carbon number and density of diesel fuel, while the PRF components for gasoline are a C 7 and a C 8 hydrocarbon. Both scales are similar in that each has a very easily ignited PRF n-alkane molecule, n-heptane (n-C 7 H 16 ) in the case of gasoline and n-hexadecane (n-C 16 H 34 , n-cetane) in the case of diesel fuel, and each has a highly branched iso-alkane component that is difficult to ignite, specifically iso-octane (2,2,4-trimethyl pentane, i-C 8 H 18 ) for gasoline and iso-cetane an ON of 100, while n-heptane has an ON equal to zero.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The high-temperature mechanism for 2-methylhexane oxidation was initially proposed by Westbrook et al 17 as part of an experimental and modeling study on the heptane isomers. Later, Sarathy et al 18 updated this mechanism and added low-temperature oxidation pathways based on Curran et al's models for n-heptane and iso-octane 8,19 .…”
Section: Introductionmentioning
confidence: 99%
“…In a rapid compression machine ignition study of the heptane isomers (φ = 1, P = 15 atm, 650 K to 950 K), Silke et al [21] showed that di-methylated heptane isomers exhibit lower reactivity when compared to mono-methylated and normal heptane isomers. In a series of comprehensive kinetic modeling studies on the autoignition of heptane isomers, Westbrook et al [22,23] also showed that the reactivity of di-methylated heptane isomers was lower than that of mono-methylated and normal heptane isomers at low and intermediate temperatures; however, at higher temperatures, their model predicted that all heptane isomers display the same ignition characteristics, which was later confirmed experimentally by Smith et al [5]. Not surprisingly, the aforementioned studies showed that the ignition behavior of heptane isomers in the negative temperature coefficient (NTC) region correlates with the research octane number (RON) of the fuel, which was also shown by Morley [24].…”
Section: Introductionmentioning
confidence: 99%